Environmental Degradation Analysis of Former Bengawan Solo River Lake Ecosystem - Ade Yudono, Andi Renata; Suntoro, Suntoro; Danisworo, Conrad; Ikhsan, Cahyono (Indonesian Journal of Geography, 2024)
The ecosystem of the former river section lake in the research area formed by the straightening of the river and located in the Sub-Urban area, faces significant environmental degradation such as pollution, erosion, and water shrinkage that threaten its sustainability. The magnitude of environmental degradation that occurs needs to be studied because it can result in a reduction in clean water and shallowing of the lake. Compared with lakes such as Poyang Lake in China, which has experienced a decline in water quantity and quality due to seasonal fluctuations, climate change and waste, this study offers a similar perspective by highlighting the interaction of natural and human factors, and adds a new dimension related to degradation caused by erosion. This study uses a comprehensive approach, namely by combining image analysis, field measurements using measuring sticks, USV, geodetic GPS, laboratory analysis, and interviews. The results of the study indicate that the lake water quality status ranges from "moderately polluted" to "heavily polluted," while the groundwater quality varies from "meets quality standards" to "lightly polluted." The high water quality status is caused by human activities and land conditions, as well as the high rate of erosion around the lake reaching 289.63 tons/ha/year, with an average soil loss of 0.11 tons/year. In addition, the lake in the study area has shrunk by up to 72% due to seasonal fluctuations and climate change. Based on this, effective management is needed to maintain the ecological balance and environmental health of the former river section lake.